Influence of CHSE Certification in Shaping Guest’s Protection Motivation Appraisals and Intention to Stay - Widarsyah, Redha; Handijaya, Made; Tuguinay, Jovanie (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThis research article aims to examine Indonesian hotel guests’ appraisal toward their intention to stay at CHSE-certified Hotels in Indonesia. The Indonesian Government introduced the Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) certification to ensure the. Three years after its first implementation in 2020, there has been very limited understanding of the influence of CHSE certification on guests’ behavior, and protection and motivations perceptions. Drawing from the Protection Motivation Theory, this research aims to examine the influence of CHSE certification on guests’ protection- motivation attitudes, and their intention to stay in CHSE-certified hotels. Analyzing a sample of 370 online survey responses generated through Populix, hypothesis testing found that guests’ perceived severity, self-efficacy, and response cost significantly and positively influenced their intention to stay. Results imply that the implementation of CHSE certification has increased guests’ awareness of the severity of Covid-19’s effects on public health. Additionally, the certification encourages guest protection (self-efficacy) and abides by the suggested and required protocols (response cost). Practical and research implications and future research suggestions of the study are discussed.ABSTRAKArtikel riset ini bertujuan untuk meneliti penilaian psikologis tamu hotel Indonesia terhadap perilaku intensi dia untuk tinggal di Hotel bersertifikasi CHSE di Indonesia. Pemerintah Indonesia memperkenalkan sertifikasi Kebersihan, Kesehatan, Keselamatan, dan Kelestarian Lingkungan (CHSE) untuk memastikan keamanan kesehatan masyarakat dan keselamatan perusahaan pariwisata, termasuk akomodasi, untuk beroperasi. Tiga tahun setelah penerapannya yang pertama, masih terdapat pemahaman yang terbatas mengenai pengaruh sertifikasi CHSE terhadap perilaku tamu, serta persepsi perlindungan dan motivasi. Berdasarkan Teori Motivasi Perlindungan, penelitian ini bertujuan untuk menguji pengaruh sertifikasi CHSE terhadap sikap motivasi perlindungan para tamu, dan niat mereka untuk menginap di hotel bersertifikat CHSE. Menganalisis sampel dari 370 tanggapan survei online yang dihasilkan melalui Populix, pengujian hipotesis menemukan bahwa tingkat keparahan yang dirasakan tamu, efikasi diri, dan biaya respons secara signifikan dan positif mempengaruhi niat mereka untuk menginap. Hasil penelitian ini menyiratkan bahwa penerapan sertifikasi CHSE telah meningkatkan kesadaran para tamu akan tingkat keparahan dampak Covid-19 terhadap kesehatan masyarakat. Selain itu, sertifikasi ini mendorong perlindungan tamu (self-efficacy) dan mematuhi protokol yang disarankan dan diwajibkan (response cost). Implikasi praktis dan penelitian serta saran penelitian di masa depan dari penelitian ini juga dibahas.